Oxidative Alkynylation of Imines with Alkynylcopper Reagents: A Straightforward and Practical Entry to Ynimines - Laouiti, Anouar; Jouvin, Kévin; Bourdreux, Flavien; Rammah, Mohamed M.; Rammah, Mohamed B.; Evano, Gwilherm (Synthesis, 2012)
We have developed an efficient and general synthesis of ynimines based on an oxidative cross-coupling between imines and alkynylcopper reagents. Upon simple addition of 1,2-dimethylimidazole in the presence of oxygen, these bench-stable, crystalline, and readily available polymeric compounds were found to be especially suitable reagents for the introduction of an alkynyl group into a wide range of ketimines at room temperature and under especially mild conditions.
Keywords: copper; cross coupling; alkynes; imines; organometallic reagents; oxidation